Quantification of Cry1Ac Protein in Bt Eggplant Fruits - Khatun, M.M.; Hasan, M.K.; Jamil, M.K.; Khanam, D. (International Journal of Applied Sciences and Biotechnology, 2017)
The cultivation of genetically engineered crops has been expanded rapidly in worldwide in a very short span of time. Bt eggplant is a transgenic eggplant created by inserting a crystal protein gene Cry1Ac from the soil bacterium Bacillus thuringiensis. Four Bt eggplant varieties - BARI Bt Eggplant-1, BARI Bt Eggplant-2, BARI Bt Eggplant-3 and BARI Bt Eggplant-4 are started to cultivate in Bangladesh in 2014 as first genetically engineered crop in the country. In the present study, ELISA technique was adopted to quantify the Cry1Ac proteins in the fruits of newly released four Bt eggplant varieties. The expression of Cry1Ac was found among the fruits of the varieties varied from 29.53 to 33.99 µg g-1. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 356-360